Ten-year evaluation of an immersive global health medical school course using a four-principle equity framework - Martin, Marie H.; Rose, Elizabeth S.; Jahangir, Eiman; Heimburger, Douglas C. (Frontiers in Education, 2023)
Responding to a growing need for health care professionals equipped with global expertise in local and international settings, an innovative global health medical school course was developed that combines rigorous didactics, mentorship, cross-cultural training, and international experiences to build students' cultural humility and clinical skills. Recognizing that global health service trips and courses can unintentionally exacerbate inequities and power imbalances, this course was evaluated using the four principles of Melby et al.'s Guidelines for Implementing Short-term Experiences in Global Health. These principles include skill building in cross-cultural effectiveness and cultural humility, bidirectional participatory relationships, local capacity building, and long-term sustainability. The course was developed with long-standing global partners and includes a capstone project that is intended to strengthen local capacity with benefits to the site and student. Student course evaluations, supervisors' observations of students, and supervisor feedback forms indicate that this course achieves these principles. Furthermore, there is evidence that students developed cultural humility, acquired foundational science knowledge and relevant skills, and changed their medical practice. This approach could serve as a model for institutions seeking to enhance training in global health for medical students.